(untitled) (Global Journal of Management and Business Research, 2018)
The main objective of this study was to investigate the challenges of supply chain integration in Ethiopia soap and detergent manufacturing companies. To address the research objective, the quantitative survey approach was followed, and target unit of analysis of the study was 25 soap and detergent manufacturing companies. The questionnaire was administered to 75 target respondents to collect the primary data (each company represented by three informants). To analyze the data obtained from respondents’ simple descriptive statistics were applied. Finally, the study found that inflexible organization system, lack of channel trust and commitment, resistance to change and lack of top management commitment were found as supply chain integration challenges in soap and detergent manufacturing firms. In general, the conclusion obtained from this study may not be used to generalize to overall supply chain network performance since its focus is only from the manufacturer’s points of view.